Reflecting on Malaysian teacher trainees’ journals - Yaacob, Aizan; Walters, Lynne Masel; Md Ali, Ruzlan; Shaik Abdullah, Sarimah; Walters, Timothy (Universiti Utara Malaysia Press, 2014)
Purpose – In this study, 37 English Language Teaching (ELT) teacher trainees from a Malaysian university conducted an action-research project to determine whether journals kept during their fieldwork in primary schools located in an area close to the university allowed them to reflect on their beliefs and behaviors in the classroom. Methodology – Themes were revealed using emergent coding in their journals. Van Manen’s (1977) three-stage model (practical, technical and critical) was used to determine the issues raised and the level of critical reflection reached in the journal entries Findings – The findings indicated that the teacher trainees demonstrated practical and technical level thinking, but rarely rose to the critical level of reflection. Nonetheless, they also demonstrated changes in their beliefs and behaviours, essential for professional development.Significance – Reflective thinking is critical to teaching and is important in the United States and in countries striving to replicate its pedagogical tools and techniques. However, many Western practices associated with the nurturing of critical thinking are not familiar to Malaysian teacher trainees.We conclude that prospective teachers here do use their journals to reflect on their educational practice, but not at the deepest levels of insight. Critical thinking must be taught to Malaysian teacher trainees and filtered through the local culture if it is to improve teaching and learning in the nation’s classrooms.